Problem Identification of Dyspraxia Students in Primary School - yustri mindaryani, yustri; Choiriyah Widyasari; Minsih (Jurnal Elementaria Edukasia, 2024)
This research aims to describe the problem identification of dyspraxic students in primary schools. In identifying the problems of students with dyspraxia in elementary school, it provides knowledge related to learning obstacles in elementary school. The type of research conducted is a qualitative case study at SDIT Muhammadiyah Al Kautsar. The data sources in this study are classes that have children with special needs, class teachers and Counselling Guidance (BK) teachers. Data collection in this study was through observations and interviews with class teachers and Counselling Guidance teachers at SDIT Muhammadiyah Al Kautsar. The results of this study indicate that SDIT Muhammadiyah Al Kautsar has carried out activities to identify the problems of students with dyspraxia and provide solutions to students with dyspraxia. In addition, the results of this study are that SDIT Muhammadiyah Al Kautsar has identified students by adjusting the curriculum, mapping of children with dyspraxia, and providing evaluations or solutions in learning obstacles for students with dyspraxia. In problem identification activities, students with dyspraxia need special handling from class teachers and Counselling Guidance teachers with the aim that students are able to learn well to achieve differentiated learning objectives. In addition, in this identification it is necessary to specifically handle and provide good training starting from writing for children with dyspraxia, special assistance strategy activities, activities up and down stairs, fine motor assistance, and making appropriate LKPD.